Money Politic, Gratifikasi, Dan Hadiah Perspektif Al-Isfahani Dalam Kitab Al-Mufradât Fî Gharîb Al-Qur’ân - Saefudin, Asep; Muid N, Abd.; Kerwanto, Kerwanto (International Journal Labs, 2025)
The Qur'an condemns money politics and gratuities as reprehensible practices. These are considered to involve the wrongful use of wealth (al-akl bi al-bâthil), al-suht (consuming wealth through manipulation of the truth), al-hadiyyah (gifts that have the potential to create conflicts of interest), al-ghulûl (misuse of authority), yasytarûna bihî tsamanan qalîla (manipulating the truth for worldly gain), and al-khiyânah (abuse of power). Most interpreters associate these key terms with bribery (risywah), which differs from gifts, a practice regarded as commendable in the Qur'an. However, caution is advised as the term